MATERIAL CULTURE AND FOOD: THE EVOLUTION OF TABLEWARE AND THE CONSOLIDATION OF BEHAVIORS DURING THE MEALTIME - Jaqueline Sayuri Nishimura; Shirley Gomes Queiroz (Universidade do Estado do Rio de Janeiro, 2016)
Consuming food is not the simple satisfaction of a nutritional and biological need, but it is also a mean of cultural expression, as it is permeated by conventions that stipulate behaviour standards and convey messages. The sharing of a meal is also a source of pleasure, and it plays a significant role in building and in the consolidation of social relations. The context of food eating, it is important to consider that, not only the type of food consumed, the amount or the way it is prepared, but also the circumstances of consumption should be given an equal importance. The utensils, their disposal at the table, the way of handling, order of use, among other protocols reflect symbologies inherited over the centuries and contribute to shape the contact between diner and food. This article proposes that the contextual interaction with the utensils applied in food consumption gradually consolidates certain habits and collaborates in identity construction, as variations in material culture result in distinct ways of dealing with food. An approach from a European starting point is taken, for its vast influence both in Brazil and worldwide, since the period of maritime expansion and colonization, in which their habits and products were widespread. In addition to an analysis of the evolution and diversification of the apparatuses used during the meals, and the intrinsic development of etiquette rules, it follows a brief exposition of the influences of such manners on the Brazilian table. DOI: 10.12957/demetra.2016.22229